Môi trường lương thực thực phẩm tại Việt Nam: Phân tích và làm rõ bức tranh chính sách quốc gia - Even, Brice; Truong Thi, Thu Trang; Nguyen Thu, Duong; Pham Thi, Huong Mai; Thai, Hang Thi Minh; Viet Anh, Bui Thi; Bene, Christophe (2025)
This policy brief presents a comprehensive assessment of Vietnam’s national food environment policy landscape, using the INFORMAS Food-EPI framework. As Vietnam’s food environments undergo rapid transformation, the brief highlights persistent regulatory gaps in key domains such as food marketing, nutritional labeling, procurement standards, and fiscal policy. While food safety regulations have advanced, policies to improve the nutritional quality, affordability, and accessibility of healthy foods remain underdeveloped. The brief calls for stronger, more coherent policy action that goes beyond consumer education to address structural drivers of unhealthy diets. It outlines five priority areas for reform: strengthening nutrition standards for processed foods; rebalancing modern retail expansion with support for informal and traditional food outlets; tightening regulations on food marketing and labeling; introducing fiscal measures to make healthy diets more affordable; and evaluating and improving the implementation of current nutrition-related policies. The findings aim to support policymakers and stakeholders working to create healthier, more equitable food systems in Vietnam.